New Results for Set-Valued Mappings on Ordered Metric Spaces - F. Sabetghadam; H. P. Masiha; H. Aydi (Journal of Function Spaces)
We establish some new fixed point results for order-closed multivalued mappings in complete metric spaces endowed with a partial order.